Invisible ADHD : proven mood and life management for smart yet scattered women - Pearson, Shanna (Flatiron Books, 2025)
"ADHD is diagnosed three times less frequently in girls and women than in boys and men, although it is equally common in both. For that reason, and because women are more likely to have the inattentive form of ADHD than the disruptive hyperactive form generally diagnosed in boys, their struggles are often invisible to the outside world. Internally, it is a different story. Because their dopamine-starved brains are always seeking stimulus, drama and chaos seem to follow them from their work and home lives to their personal relationships. The outward manifestations of these internal symptoms-indecision, emotional fragility, habitual lateness, or confrontational behaviors- earn countless creative, intelligent, and hardworking women labels like "drama queen," "flaky," or just plain unreliable. As a result, many find themselves stuck in life, unable to achieve the personal and professional goals that seem to come to others so effortlessly. After after being diagnosed with ADHD in her twenties, Pearson has dedicated her career to helping others harness the strengths and manage the challenges of living with ADHD. In Invisible ADHD, she writes from the perspective and knowledge of what actually works, based on deep experience with more than a hundred thousand individual coaching sessions over the course of two decades, and a lifetime of mastering her own severe ADHD. Using proprietary strategies and exercises developed to help her clients succeed in love, life, and business, Pearson's straight-shooting book will help any woman who struggles with the symptoms of ADHD to communicate better, strengthen personal and professional bonds, and learn to trust herself enough to reach for what she truly wants in life"-- Provided by publisher.